Establishing content and Face Validity of a developed educational module: life skill-based education for improving emotional health and coping mechanisms among adolescents in Malaysian orphanages - Mohammadzadeh, Marjan; Awang, Hamidin; Ismail, Suriani; Kadir Shahar, Hayati (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: The current study as a part of our investigation on improving emotional and behavioural health in Malaysian orphanages was aimed to establish Content Validity Index (CVI) as well as Face Validity of a new life skill-based module for improving emotional health and coping mechanisms in Malaysian Institutionalised Adolescents including 2 different parts. Methods: In order to assess the content validity and using a 16-item questionnaire, the initial version of the module was reviewed by 9 experts in the area. In the second part, the face validity of the module was assessed among 30 adolescents aged 14-17 from 2 orphanages. Using Depression, Anxiety, Stress Scale (DASS21) and Brief COPE scale as the study instruments, the emotional heath and coping mechanisms among the participants was investigated before and after a life skills workshop (pre- and post-test). The activities in the workshop were randomly selected from the module activities. Results: Results of the first part of study showed the minimum Value of the Item-level Content Validity Index and the computed the sum of items (S-CVI) for the study module were 0.78 and 0.93 respectively. The results of the second part of study showed the selected activities from module were significantly change the coping mechanisms expect substance use, behavior disengagement, venting, humor and religion (p>0.05). Furthermore, the mean score of anxiety (t=5.39, P<0.001) and stress (t=3.90, P<0.001) significantly decreased among the participants in post-test but there was no significant change on the mean score of depression (t=0.50, P=0.59). Conclusion: both contend and face validity of the developed module were approved.